Understanding Risky Behavior: The Influence of Cognitive, Emotional and Hormonal Factors on Decision-Making under Risk - Kusev, Petko; Purser, Harry; Heilman, Renata; Cooke, Alex J.; Van Schaik, Paul; Baranova, Victoria; Martin, Rose; Ayton, Peter (Frontiers in Psychology, 2017)
Financial risky decisions and evaluations pervade many human everyday activities. Scientific research in such decision-making typically explores the influence of socio-economic and cognitive factors on financial behavior. However, very little research has explored the holistic influence of contextual, emotional, and hormonal factors on preferences for risk in insurance and investment behaviors. Accordingly, the goal of this review article is to address the complexity of individual risky behavior and its underlying psychological factors, as well as to critically examine current regulations on financial behavior.